Polysaccharides of Marine Algae in the Correction of Disorders Associated with Metabolic Syndrome - N. N. Besednova; S. P. Kryzhanovskiy; T. N. Zvyagintseva; YE. V. Persiyanova; I. A. Korneeva (Антибиотики и Химиотерапия, 2020)
This review provides information on the effects of sulfated polysaccharides (SPS) derived from algae on the components of the metabolic syndrome (obesity, lipid metabolism, type 2 diabetes, hypertension) and the possibility of correcting disorders associated with this condition, as well as socially significant diseases associated with it. There are few studies of the effectiveness of these compounds conducted in a clinical setting, although in terms of their pharmacological action (antidyslipidemic, immunomodulatory, anti-inflammatory, hypoglycemic, etc.) they are comparable with medications (with statins, in particular), as for health safety, they are most commonly superior to those medications. The authors draw attention to the fact that seaweed-derived SPS can be the basis for the creation of medications, dietary supplements, as well as functional foods for patients with metabolic syndrome.